Gas-puff induced cold pulse propagation in ADITYA-U tokamak. (12th August 2021) - Macwan, Tanmay; Raj, Harshita; Singh, Kaushlender; Dolui, Suman; Patel, Sharvil; Kumar, Ankit; Gautam, P.; Ghosh, J.; Tanna, R.L.; Jadeja, K.A.; Patel, K.M.; Kumar, Rohit; et al.
Abstract: Short bursts (∼1 ms) of gas, injecting ∼10 17 –10 18 molecules of hydrogen and/or deuterium, lead to the observation of cold pulse propagation phenomenon in hydrogen plasmas of the ADITYA-U tokamak. After every injection, a sharp increase in the chord-averaged density is observed followed by an increase in the core electron temperature. Simultaneously, the electron density and temperature decrease at the edge. All these observations are characteristics of cold pulse propagation due to the pulsed gas application. The increase in the core temperature is observed to depend on the values of both the chord-averaged plasma density at the instant of gas-injection and the amount of gas injected below a threshold value. Increasing the amount of gas-puff leads to higher increments in the core-density and the core-temperature. Interestingly, the rates of rise of density and temperature remain the same. The gas-puff also leads to a fast decrease in the radially outward electric field together with a rapid increase in the loop-voltage suggesting a reduction in the ion-orbit loss and an increase in Ware-pinch. This may explain the sharp density rise, which remains mostly independent of the toroidal magnetic field and plasma current in the experiment. Application of a subsequent gas-puff before the effect of the previous gas-pulse dies down, leads to an increase in the overall electron density and consequently the energy confinement time.